Whole genome sequencing of vancomycin resistant Enterococcus faecium isolated from cat and dog - Aslantaş, Ö; Televi, H; Büyükaltay, K; Tek, E (Journal of the Hellenic Veterinary Medical Society, 2025)
Vancomycin-resistant enterococci (VRE) have emerged as a significant increasingly become an public health concern over past few decades due to their association with serious multidrug-resistant (MDR) infections. This study utilized whole genome sequencing (WGS) to perform molecular characterization of three VRE isolates previously recovered from two cats and one dog. The genomic DNA of the isolates was extracted and sequencing was performed using the Illumina Novaseq platform. The genomes of Enterococcus faecium HMKU_VREfm_Dog12, Enterococcus faecium HMKU_VREfm_Cat95 and Enterococcus faecium HMKU_VREfm_Cat103 consisted of 2707111 bp, 2715129 bp, and 2664256 bp, respectively with GC content of 37.95%, 38.03% and 38.01%, respectively. Multidrug antimicrobial resistance genes conferring resistance to aminoglycosides (aac(6’)-aph(2’) and ant(6)-Ia), lincosamides (lnu(B) and lsa(E)), macrolides (erm(A), erm(B), msr(A), msr(C), and msr(B)), trimethoprim (dfrG) and tetracyclines (tet(L) and tet(M)) were identified. The sequence type (ST) of each isolate was determined using the Enterococcus PubMLST database. The isolates were found to belong to different STs (ST2248 in VREfm_Dog12, ST43 in VREfm_Cat95, and ST284 in VREfm_Cat103). The isolates carried only efaAfm (adhesion-associated protein) as virulence gene. To the best of the authors’ knowledge, this study is the first to provide insights into genetic diversity of VREfm strains isolated from dogs and cats using whole genome sequencing analysis in Turkey. The findings underscore the importance of genomic surveillance in monitoring the dissemination of MDR VREfm in pet animals.